2018
DOI: 10.3389/fpsyg.2017.02346
|View full text |Cite
|
Sign up to set email alerts
|

Grade Expectations: Rationality and Overconfidence

Abstract: Confidence and overconfidence are essential aspects of human nature, but measuring (over)confidence is not easy. Our approach is to consider students' forecasts of their exam grades. Part of a student's grade expectation is based on the student's previous academic achievements; what remains can be interpreted as (over)confidence. Our results are based on a sample of about 500 second-year undergraduate students enrolled in a statistics course in Moscow. The course contains three exams and each student produces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 31 publications
0
17
0
4
Order By: Relevance
“…Because this assignment is built around students constructing species and biodiversity literacy over the semester, their anticipated grade reflects, in part, their competency in those areas. Although this overconfidence in evaluating their work is common, overconfidence can negatively affect both personal and academic development (Hall and Sverdlik 2016;Magnus and Peresetsky 2018;Deslauriers et al 2019). Closer examination of rubric scores revealed that the lower earned grade was mostly due to inaccurate identifications (at both the family and species level), sloppy citations of identification sources, and poor organization and curation of the collection (even a digital collection needs to be organized and curated properly) (Figure 2).…”
Section: Assessmentsmentioning
confidence: 99%
“…Because this assignment is built around students constructing species and biodiversity literacy over the semester, their anticipated grade reflects, in part, their competency in those areas. Although this overconfidence in evaluating their work is common, overconfidence can negatively affect both personal and academic development (Hall and Sverdlik 2016;Magnus and Peresetsky 2018;Deslauriers et al 2019). Closer examination of rubric scores revealed that the lower earned grade was mostly due to inaccurate identifications (at both the family and species level), sloppy citations of identification sources, and poor organization and curation of the collection (even a digital collection needs to be organized and curated properly) (Figure 2).…”
Section: Assessmentsmentioning
confidence: 99%
“…As a result of the procedure and the possibility of a bonus, the response rate was extremely high (97%). The idea of giving each student an incentive to express their opinion was successfully used earlier in experiments by Blackwell (2010) and Magnus and Peresetsky (2018).…”
Section: The Datamentioning
confidence: 99%
“…It has been shown that an overconfident student performs better than a student of equal ability that does not exhibit overconfidence. The argument is that such students will work harder in an attempt to fulfil their high expectations (c.f., Ballard and Johnson 2005; Johnson and Fowler 2011; Magnus and Peresetsky 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(2017) show that beliefs about academic performance tend to persist. Magnus and Peresetsky (2018) showed that while there is persistence in overconfidence, women tend to learn and adjust more quickly than men.…”
Section: Introductionmentioning
confidence: 99%